Saint Odd [compact disc, unabridged] : an Odd Thomas novel - Koontz, Dean R. (Dean Ray), 1945- (Koontz, Dean R. (Dean Ray), 1945- Odd Thomas novel., 2014)
Odd Thomas is back where it all started . . . because the time has come to finish it. Since he left his simple life in the small town of Pico Mundo, California, his journey has taken him to places strange and wonderful, mysterious and terrifying. Across the land, in the company of mortals and spirits alike, he has known kindness and cruelty, felt love and loss, saved lives and taken them-as he's borne witness to humanity's greatest good and darkest evil.